KEPENTINGAN INDONESIA DALAM KERJA SAMA BILATERAL DENGAN JEPANG STUDI KASUS: INDONESIA-JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) - Yusron Avivi; Muhnizar Siagian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2020)
The Indonesia-Japan Economic Partnership Agreement (IJEPA) is a bilateral cooperation in the economic sector between Indonesia and Japan that is expected to support economic growth between the two countries through various established schemes. In foreign policy studies, each country has an interest to be achieved in a variety of bilateral cooperation undertaken. Indonesia has many national interests in this bilateral economic cooperation. And also the various factors behind Indonesia to pursue economic diplomacy through bilateral economic cooperation agreements with Japan. This study aims to look at Indonesia's national interests in IJEPA cooperation and how Indonesia is trying to achieve these various interests. This study uses a qualitative case study method with descriptive analytical methods. Researchers used a foreign policy approach with various concepts of national interest in bilateral cooperation in the economic field.